Sodium hypochlorite generator cathode material prepared through diaphragm-free electrolysis and preparation method of sodium hypochlorite generator cathode material

A composite cathode material using a three-dimensional porous stainless steel fiber felt matrix with carbon fibers and aerogel or polyaniline-carbon nanotube coatings addresses corrosion issues in diaphragm-free electrolysis, enhancing stability and efficiency in sodium hypochlorite production.

CN119243206APending Publication Date: 2025-01-03CHINA SALT CHANGZHOU CHEM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411523449.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Diaphragm-free electrolysis methods for sodium hypochlorite production face challenges due to corrosion of stainless steel cathodes when the generator is shut down, affecting product quality and efficiency, and existing cathode materials lack sufficient corrosion resistance and conductivity under high current density.

Method used

A cathode material composed of a three-dimensional porous stainless steel fiber felt matrix entangled with carbon fibers and coated with a carbon aerogel or polyaniline-carbon nanotube composite aerogel layer, optimizing pore size, porosity, and conductivity to enhance corrosion resistance and electrochemical performance.

Benefits of technology

The composite cathode material maintains stability and efficiency in harsh electrolysis environments, reducing corrosion and extending the service life of the electrode, thereby improving sodium hypochlorite production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of sodium hypochlorite production, in particular to a sodium hypochlorite generator cathode material prepared through diaphragm-free electrolysis and a preparation method of the sodium hypochlorite generator cathode material. The invention relates to a sodium hypochlorite generator cathode material prepared by diaphragm-free electrolysis. The sodium hypochlorite generator cathode material comprises a three-dimensional porous stainless steel fiber felt matrix and carbon fibers entangled with the three-dimensional porous stainless steel fiber felt matrix. The stable material is formed by entangling the carbon fibers and the three-dimensional porous stainless steel fiber felt, meanwhile, the carbon fibers have high electrochemical stability, the oxidation process of stainless steel can be slowed down to a certain degree, and the corrosion resistance of the stainless steel is improved. And meanwhile, the conductivity and the strength of the electrode are further enhanced through combination with the carbon fibers, and the stability under the condition of high current density is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium hypochlorite production, in particular to a cathode material for preparing a sodium hypochlorite generator by diaphragm-free electrolysis and a preparation method thereof. Background Art

[0002] Sodium hypochlorite can be prepared by electrolyzing low-concentration sodium chloride solution without diaphragm. The solution is electrolyzed under the action of direct current, chlorine is produced at the anode in the cell, and sodium hydroxide and hydrogen are produced at the cathode. The two products contact and react to form a sodium hypochlorite solution. In a diaphragm-free electrolytic cell, the electrolyte is quickly injected between two parallel electrode plates by a pump to obtain a large volume and low concentration of NaClO, because the maximum concentration of hypochlorite that can be obtained is limited by side reactions. At present, most electrolysis experimental methods are diaphragm methods, but diaphragm-free methods are rarely used, mainly because the diaphragm method increases the yield of electrolysis experiments, but considering that diaphragm-free electrolytic cells are more economical than diaphragm electrolytic cells, they have the advantages of being able to reduce cell voltage, reduce energy consumption, and simple operation.

[0003] Stainless steel cathode material refers to the cathode part used in electrochemical reactions, usually made of stainless steel. It is widely used in various electrochemical equipment and industrial processes due to its excellent corrosion resistance and conductivity. The corrosion resistance of stainless steel mainly comes from its alloying elements, such as chromium and nickel. The passivation film formed by these elements can effectively prevent the metal matrix from being corroded and extend the service life of the cathode. However, in the actual production process, after the sodium hypochlorite generator has been shut down for a period of time, if the sodium hypochlorite solution in the electrolytic cell is not drained in time, the cathode stainless steel material in the electrolytic cell will appear black water due to the corrosion of the sodium hypochlorite solution every time the generator is turned on, which affects the product quality and production efficiency of sodium hypochlorite. Summary of the invention

[0004] In order to improve the above technical problems, the present application provides a cathode material for a sodium hypochlorite generator prepared by diaphragm-free electrolysis and a preparation method thereof.

[0005] A method for preparing a cathode material for a sodium hypochlorite generator by diaphragm-free electrolysis adopts the following technical solution: A cathode material for a sodium hypochlorite generator prepared by diaphragm-free electrolysis comprises a three-dimensional porous stainless steel fiber felt matrix and carbon fibers entangled with the three-dimensional porous stainless steel fiber felt matrix.

[0006] Through the above technical solution, the present application uses three-dimensional porous stainless steel fiber felt as a matrix and entangles it with carbon fiber to form a new type of composite structure. The three-dimensional porous stainless steel fiber felt has excellent corrosion resistance and mechanical strength, and can provide stable support during the electrolysis process. At the same time, its porous structure can provide a large specific surface area, so that the contact area between the electrolyte and the electrode surface is increased, thereby improving the efficiency of the electrochemical reaction.

[0007] The present application forms a stable material by entanglement of carbon fiber and three-dimensional porous stainless steel fiber felt. At the same time, the carbon fiber itself has high electrochemical stability, which can slow down the oxidation process of stainless steel to a certain extent and improve its corrosion resistance. At the same time, the combination with carbon fiber further enhances the conductivity and the strength of the electrode, ensuring stability under high current density.

[0008] Furthermore, the carbon fiber has a diameter of 0.1-4.0 μm.

[0009] Through the above technical solution, the present application optimizes the diameter size of carbon fiber, and carbon fiber of this size can provide a larger specific surface area, increase active sites, and thus increase the rate of electrochemical reaction. In addition, thinner carbon fibers can form a tighter network structure in the three-dimensional matrix, enhance overall strength, and reduce the risk of electrode damage at high current density. This design allows the electrode material to maintain a high stability in a harsh electrolysis environment, improving operational convenience and safety.

[0010] Furthermore, the three-dimensional porous stainless steel fiber felt matrix has an average pore size of 15-20 μm and a porosity of 75-85%.

[0011] Through the above technical solution, the application optimizes the average pore size and porosity of the three-dimensional porous stainless steel fiber felt matrix, which helps to improve the fluidity of the electrolyte, so that the reactants can better contact the electrode surface, thereby increasing the reaction rate. The overall performance of the electrode material is optimized to ensure that it always has stable reaction capacity during long-term use, making the sodium hypochlorite generation process more efficient and reliable.

[0012] Furthermore, the surface of the three-dimensional porous stainless steel fiber felt matrix is ​​also coated with a corrosion-resistant modified layer, and the corrosion-resistant modified layer is a carbon aerogel coating layer.

[0013] Furthermore, the carbon aerogel coating layer is made by the following scheme: The oxidized cellulose is mixed with deionized water and homogenized, the homogenized solution is collected and carbon nanotubes are added, the mixture is stirred and placed in an ultrasonic cell crusher, dispersed and the dispersion is collected; The three-dimensional porous stainless steel fiber felt substrate is immersed in the dispersion liquid. After the impregnation is completed, it is placed in a tubular furnace, heated and placed under the protection of inert gas for carbonization treatment to prepare a carbon aerogel coating layer.

[0014] Through the above technical solution, the present application optimizes the surface structure of the three-dimensional porous stainless steel fiber felt matrix, and by coating the corrosion-resistant modified layer on the surface of the three-dimensional porous stainless steel fiber felt matrix, it can provide effective chemical protection during the electrolysis process, especially in a high chloride ion environment, by introducing a carbon aerogel layer, which significantly improves the corrosion resistance of the electrode and thus extends its service life. In addition, the porous characteristics of the carbon aerogel not only help to maintain good electrical conductivity, but also promote the diffusion of reactants and improve the electrochemical activity of the electrode. This corrosion-resistant modification design provides a strong guarantee for the cathode material, allowing it to still operate stably in harsh electrolysis environments and improve the production efficiency of sodium hypochlorite.

[0015] Furthermore, the corrosion-resistant modified layer is a polyaniline-carbon nanotube composite aerogel coating layer.

[0016] Furthermore, the polyaniline-carbon nanotube composite aerogel coating layer is made by the following scheme: Place carbon nanotubes in deionized water, disperse them by ultrasonic, add polyvinyl alcohol, stir and mix, and collect the dispersion; Take the dispersion and add aniline monomer, ammonium persulfate and 8% hydrochloric acid by mass, stir and mix and keep warm for reaction, collect the reaction liquid and immerse the three-dimensional porous stainless steel fiber felt matrix in the reaction liquid. After the impregnation is completed, freeze it with liquid nitrogen and place it at -5°C for low-temperature polymerization. After the polymerization is completed, thaw the sample and remove impurities, and vacuum freeze-dry it to prepare the polyaniline-carbon nanotube composite aerogel coating.

[0017] Through the above technical solution, the present application further improves the performance of the cathode material by introducing a polyaniline-carbon nanotube composite aerogel coating layer. Polyaniline, as a conductive polymer, has excellent conductivity, and the composite with carbon nanotubes not only enhances the overall conductivity, but also improves the thermal stability and antioxidant properties of the material. This composite material can show higher stability and efficiency in electrochemical reactions, especially in harsh electrolytic environments. Through this modification, the cathode material can more effectively promote the generation of sodium hypochlorite while extending its service life.

[0018] Furthermore, the mass ratio of the aniline monomer, ammonium persulfate and 8% hydrochloric acid is (150-200): (400-500): (80-90).

[0019] Through the above technical solution, the present application optimizes the synthesis reaction conditions of polyaniline-carbon nanotube composite aerogel. Through a reasonable mass ratio, the sufficiency of the polymerization reaction is ensured, thereby improving the conductivity and stability of the material. In addition, optimizing the reaction conditions helps to improve the degree of polymerization and uniformity, so that the material exhibits better conductivity and corrosion resistance in the electrochemical reaction.

[0020] In summary, this application has the following beneficial effects: First, the present application uses three-dimensional porous stainless steel fiber felt as a matrix and entangles it with carbon fiber to form a new type of composite structure. The three-dimensional porous stainless steel fiber felt has excellent corrosion resistance and mechanical strength, and can provide stable support during the electrolysis process. At the same time, its porous structure can provide a large specific surface area, so that the contact area between the electrolyte and the electrode surface is increased, thereby improving the efficiency of the electrochemical reaction.

[0021] The present application forms a stable material by entanglement of carbon fiber and three-dimensional porous stainless steel fiber felt. At the same time, the carbon fiber itself has high electrochemical stability, which can slow down the oxidation process of stainless steel to a certain extent and improve its corrosion resistance. At the same time, the combination with carbon fiber further enhances the conductivity and the strength of the electrode, ensuring stability under high current density.

[0022] Second, the present application optimizes the surface structure of the three-dimensional porous stainless steel fiber felt matrix, and by coating the surface of the three-dimensional porous stainless steel fiber felt matrix with a corrosion-resistant modified layer, the carbon aerogel layer can be introduced to provide effective chemical protection during the electrolysis process, especially in a high chloride ion environment, thereby significantly improving the corrosion resistance of the electrode and extending its service life. In addition, the porous properties of the carbon aerogel not only help to maintain good electrical conductivity, but also promote the diffusion of reactants and improve the electrochemical activity of the electrode. This corrosion-resistant modification design provides a strong guarantee for the cathode material, allowing it to operate stably in harsh electrolysis environments and improve the production efficiency of sodium hypochlorite.

[0023] Third, the present application further improves the performance of the cathode material by introducing a polyaniline-carbon nanotube composite aerogel coating layer. Polyaniline, as a conductive polymer, has excellent conductivity, and the composite with carbon nanotubes not only enhances the overall conductivity, but also improves the thermal stability and antioxidant properties of the material. This composite material can show higher stability and efficiency in electrochemical reactions, especially in harsh electrolytic environments. Through this modification, the cathode material can more effectively promote the generation of sodium hypochlorite while extending its service life. DETAILED DESCRIPTION

[0024] The present application is further described in detail below with reference to the embodiments.

[0025] In the examples of the present application, the raw materials and instruments used are as follows, but not limited thereto: The present application is further described in detail below with reference to the embodiments.

[0026] Example 1 The short-cut carbon fibers with a diameter of 0.1-4.0 μm and a length of 1 μm are stirred and mixed with a 5% by mass polyvinyl alcohol solution, ultrasonically dispersed and the dispersion is collected; a three-dimensional porous stainless steel fiber felt matrix with an average pore size of about 15 μm and a porosity of 75% is immersed in the dispersion, and dried at 55° C. for 6 hours to prepare the cathode material for the sodium hypochlorite generator prepared by membraneless electrolysis.

[0027] Example 2 450 g of oxidized cellulose was mixed with 1000 g of deionized water and homogenized, the homogenate was collected and 20 g of carbon nanotubes were added, the mixture was stirred and placed in an ultrasonic cell crusher, dispersed and the dispersion was collected; A three-dimensional porous stainless steel fiber felt matrix with an average pore size of 20 μm and a porosity of 85% is immersed in the dispersion. After the impregnation is completed, it is placed in a tubular furnace, heated to 400°C and placed under nitrogen protection. Carbonization treatment is performed for 5 hours to prepare a three-dimensional porous stainless steel fiber felt matrix coated with a carbon aerogel coating layer.

[0028] The short-cut carbon fibers with a diameter of 0.1-4.0 μm and a length of 1 μm are stirred and mixed with a 5% by mass polyvinyl alcohol solution, ultrasonically dispersed and the dispersion is collected; a three-dimensional porous stainless steel fiber felt matrix coated with a carbon aerogel coating layer is immersed in the dispersion, and dried at 55° C. for 6 hours to prepare the cathode material for the sodium hypochlorite generator prepared by membraneless electrolysis.

[0029] Example 3 500 g of oxidized cellulose was mixed with 1000 g of deionized water and homogenized, the homogenized liquid was collected and 25 g of carbon nanotubes were added, the mixture was stirred and placed in an ultrasonic cell crusher, dispersed and the dispersion was collected; A three-dimensional porous stainless steel fiber felt matrix with an average pore size of 20 μm and a porosity of 85% was immersed in the dispersion. After the impregnation was completed, it was placed in a tubular furnace, heated to 450°C and placed under nitrogen protection for carbonization treatment for 5 hours to prepare a three-dimensional porous stainless steel fiber felt matrix coated with a carbon aerogel coating layer.

[0030] The short-cut carbon fibers with a diameter of 0.1-4.0 μm and a length of 1 μm are stirred and mixed with a 5% by mass polyvinyl alcohol solution, ultrasonically dispersed and the dispersion is collected; a three-dimensional porous stainless steel fiber felt matrix coated with a carbon aerogel coating layer is immersed in the dispersion, and dried at 55° C. for 6 hours to prepare the cathode material for the sodium hypochlorite generator prepared by membraneless electrolysis.

[0031] Example 4 550 g of oxidized cellulose was mixed with 1000 g of deionized water and homogenized, the homogenate was collected and 30 g of carbon nanotubes were added, the mixture was stirred and placed in an ultrasonic cell crusher, dispersed and the dispersion was collected; A three-dimensional porous stainless steel fiber felt matrix with an average pore size of 20 μm and a porosity of 85% was immersed in the dispersion. After the impregnation was completed, it was placed in a tubular furnace, heated to 500°C and placed under nitrogen protection for carbonization treatment for 5 hours to prepare a three-dimensional porous stainless steel fiber felt matrix coated with a carbon aerogel coating layer.

[0032] The short-cut carbon fibers with a diameter of 0.1-4.0 μm and a length of 1 μm are stirred and mixed with a 5% by mass polyvinyl alcohol solution, ultrasonically dispersed and the dispersion is collected; a three-dimensional porous stainless steel fiber felt matrix coated with a carbon aerogel coating layer is immersed in the dispersion, and dried at 55° C. for 6 hours to prepare the cathode material for the sodium hypochlorite generator prepared by membraneless electrolysis.

[0033] Example 5 15 g of carbon nanotubes were placed in 3000 g of deionized water, and 1500 g of polyvinyl alcohol was added after ultrasonic dispersion, and the mixture was stirred and mixed, and the dispersion was collected; Take the dispersion and add 15g of aniline monomer, 40g of ammonium persulfate and 8g of 8% hydrochloric acid by mass, stir and mix, collect the reaction liquid, and immerse the three-dimensional porous stainless steel fiber felt matrix with an average pore size of 20μm and a porosity of 85% in the reaction liquid. After the impregnation is completed, freeze it with liquid nitrogen and place it at -5°C for low-temperature polymerization. After the polymerization is completed, thaw the sample and remove impurities, and vacuum freeze-dry it to prepare a polyaniline-carbon nanotube composite aerogel coating.

[0034] The short-cut carbon fibers with a diameter of 0.1-4.0 μm and a length of 1 μm are stirred and mixed with a 5% by mass polyvinyl alcohol solution, ultrasonically dispersed and the dispersion is collected; the coating layer coated with the polyaniline-carbon nanotube composite aerogel is immersed in the dispersion, and dried at 55° C. for 6 hours to prepare the cathode material for the sodium hypochlorite generator prepared by membraneless electrolysis.

[0035] Example 6 17 g of carbon nanotubes were placed in 3000 g of deionized water, and 1600 g of polyvinyl alcohol was added thereto, and the mixture was stirred and mixed, and the dispersion was collected; Take the dispersion and add 17g of aniline monomer, 45g of ammonium persulfate and 8.5g of 8% hydrochloric acid, stir and mix, collect the reaction liquid, and immerse the three-dimensional porous stainless steel fiber felt matrix with an average pore size of 20μm and a porosity of 85% in the reaction liquid. After the impregnation is completed, freeze it with liquid nitrogen and place it at -5°C for low-temperature polymerization. After the polymerization is completed, thaw the sample and remove impurities, and vacuum freeze-dry it to prepare a polyaniline-carbon nanotube composite aerogel coating.

[0036] The short-cut carbon fibers with a diameter of 0.1-4.0 μm and a length of 1 μm are stirred and mixed with a 5% by mass polyvinyl alcohol solution, ultrasonically dispersed and the dispersion is collected; the coating layer coated with the polyaniline-carbon nanotube composite aerogel is immersed in the dispersion, and dried at 55° C. for 6 hours to prepare the cathode material for the sodium hypochlorite generator prepared by membraneless electrolysis.

[0037] Example 7 20 g of carbon nanotubes were placed in 3000 g of deionized water, and 1700 g of polyvinyl alcohol was added thereto under ultrasonic dispersion, and the mixture was stirred and mixed, and the dispersion was collected; Take the dispersion and add 20g of aniline monomer, 50g of ammonium persulfate and 9g of 8% hydrochloric acid by mass, stir and mix, collect the reaction liquid, and immerse the three-dimensional porous stainless steel fiber felt matrix with an average pore size of 20μm and a porosity of 85% in the reaction liquid. After the impregnation is completed, freeze it with liquid nitrogen and place it at -5°C for low-temperature polymerization. After the polymerization is completed, thaw the sample and remove impurities, and vacuum freeze-dry it to prepare a polyaniline-carbon nanotube composite aerogel coating.

[0038] The short-cut carbon fibers with a diameter of 0.1-4.0 μm and a length of 1 μm are stirred and mixed with a 5% by mass polyvinyl alcohol solution, ultrasonically dispersed and the dispersion is collected; the coating layer coated with the polyaniline-carbon nanotube composite aerogel is immersed in the dispersion, and dried at 55° C. for 6 hours to prepare the cathode material for the sodium hypochlorite generator prepared by membraneless electrolysis.

[0039] Comparative Example 1 A three-dimensional porous stainless steel fiber felt matrix with an average pore size of 20 μm and a porosity of 85% was used as the cathode material for the preparation of sodium hypochlorite generator by diaphragmless electrolysis.

[0040] Performance Testing The cathode materials for preparing sodium hypochlorite generator by diaphragmless electrolysis prepared in Examples 1-7 and the cathode materials in Comparative Example 1 were tested for corrosion performance of the cathode materials: The electrolysis test is carried out on the electrolysis parameters such as the salt water concentration, electrolyte flow, DC current, cooling water flow, and working environment of the stainless steel cathode sodium hypochlorite generator. After the test is completed, the equipment is shut down without draining the sodium hypochlorite solution in the electrolytic cell. The equipment is kept in this state for 12 hours before being restarted. When starting up, first turn on the salt water pump and the circulating cooling water pump to discharge the sodium hypochlorite solution in the electrolytic cell. At this time, the power supply is not turned on to prevent the sodium hypochlorite solution from electrolyzing again. The turbidity of the discharged sodium hypochlorite solution is measured at shutdown, 12 hours after shutdown, and 40 minutes after shutdown.

[0041] The details are shown in Table 1 below: Table 1 Performance test table

[0042] From the results of the above Examples 1-7, Comparative Example 1 and Table 1, it can be found that: By comparing Example 1 with Comparative Example 1, it is shown that the present invention forms a stable material by entanglement of carbon fiber and three-dimensional porous stainless steel fiber felt, and the carbon fiber itself has high electrochemical stability, which can slow down the oxidation process of stainless steel to a certain extent and improve its corrosion resistance. At the same time, the combination with carbon fiber further enhances the conductivity and the strength of the electrode, ensuring stability under high current density.

[0043] By comparing Example 1 with Examples 2-4, it is shown that the present application optimizes the surface structure of the three-dimensional porous stainless steel fiber felt matrix, and by coating the surface of the three-dimensional porous stainless steel fiber felt matrix with a corrosion-resistant modified layer, the carbon aerogel layer can be introduced to provide effective chemical protection during the electrolysis process, especially in a high chloride ion environment, thereby significantly improving the corrosion resistance of the electrode and extending its service life. In addition, the porous properties of the carbon aerogel not only help to maintain good electrical conductivity, but also promote the diffusion of reactants and improve the electrochemical activity of the electrode. This corrosion-resistant modification design provides a strong guarantee for the cathode material, allowing it to still operate stably in harsh electrolysis environments and improve the production efficiency of sodium hypochlorite.

[0044] By comparing Examples 2-4 with Examples 5-7, it is further illustrated that the present application further improves the performance of the cathode material by introducing a polyaniline-carbon nanotube composite aerogel coating layer. Polyaniline, as a conductive polymer, has excellent conductivity, and the composite with carbon nanotubes not only enhances the overall conductivity, but also improves the thermal stability and antioxidant properties of the material. This composite material can show higher stability and efficiency in electrochemical reactions, especially in harsh electrolytic environments. Through this modification, the cathode material can more effectively promote the generation of sodium hypochlorite while extending its service life.

[0045] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

[0046] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.

[0047] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.

[0048] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.

Claims

1. A method for preparing a cathode material for a sodium hypochlorite generator by diaphragm-free electrolysis, characterized in that: The invention comprises a three-dimensional porous stainless steel fiber felt matrix and carbon fibers entangled with the three-dimensional porous stainless steel fiber felt matrix.

2. The method for preparing a cathode material for a sodium hypochlorite generator by diaphragm-free electrolysis according to claim 1, characterized in that: The carbon fiber has a diameter of 0.1-4.0 μm.

3. The method for preparing a cathode material for a sodium hypochlorite generator by diaphragm-free electrolysis according to claim 1, characterized in that: The three-dimensional porous stainless steel fiber felt matrix has an average pore size of 15-20 μm and a porosity of 75-85%.

4. The method for preparing a cathode material for a sodium hypochlorite generator by diaphragm-free electrolysis according to claim 1, characterized in that: The surface of the three-dimensional porous stainless steel fiber felt matrix is ​​also coated with a corrosion-resistant modified layer, and the corrosion-resistant modified layer is a carbon aerogel coating layer.

5. The method for preparing a cathode material for a sodium hypochlorite generator by diaphragm-free electrolysis according to claim 1, characterized in that: The carbon aerogel coating layer is made by the following scheme: The oxidized cellulose is mixed with deionized water and homogenized, the homogenized solution is collected and carbon nanotubes are added, the mixture is stirred and placed in an ultrasonic cell crusher, dispersed and the dispersion is collected; The three-dimensional porous stainless steel fiber felt substrate is immersed in the dispersion liquid. After the impregnation is completed, it is placed in a tubular furnace, heated and placed under the protection of inert gas for carbonization treatment to prepare a carbon aerogel coating layer.

6. The method for preparing a cathode material for a sodium hypochlorite generator by diaphragm-free electrolysis according to claim 1, characterized in that: The corrosion-resistant modified layer is a polyaniline-carbon nanotube composite aerogel coating layer.

7. The method for preparing a cathode material for a sodium hypochlorite generator by diaphragmless electrolysis according to claim 1, characterized in that: The polyaniline-carbon nanotube composite aerogel coating layer is prepared by the following scheme: Place carbon nanotubes in deionized water, disperse them by ultrasonication, add polyvinyl alcohol, stir and mix, and collect the dispersion; Take the dispersion and add aniline monomer, ammonium persulfate and 8% hydrochloric acid by mass, stir and mix and keep warm for reaction, collect the reaction liquid and immerse the three-dimensional porous stainless steel fiber felt matrix in the reaction liquid. After the impregnation is completed, freeze it with liquid nitrogen and place it at -5°C for low-temperature polymerization. After the polymerization is completed, thaw the sample and remove impurities, and vacuum freeze-dry it to prepare the polyaniline-carbon nanotube composite aerogel coating.

8. The method for preparing a cathode material for a sodium hypochlorite generator by diaphragm-free electrolysis according to claim 6, characterized in that: The mass ratio of the aniline monomer, ammonium persulfate and 8% hydrochloric acid is (150-200): (400-500): (80-90).